ANALYSIS OF THE CONCEPT OF "ASCETISM" AND ATTITUDE TO ASCETIAN PRACTICES IN RELIGIONS - Khudayberganova Gulnora (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the definitions given to the concept of asceticism, and the differences in approaches to the practical aspects of ascetic views. It has been established that each of the world's religions has a specially formed ascetic state, and this also creates mutual differences. The phenomenon of asceticism is revealed in its own way from the religious and philosophical teachings of Hinduism, Jainism, monotheistic religions, Judaism, Christianity, and Islam.